CRIMINAL LAW REFORM IN THE FACE OF THE SOCIETY 5.0 ERA AGAINST CYBER CRIME - Nopit Ernasari; Naib (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Society 5.0 brings a major transformation in the social order through the integration of advanced technologies that blur the boundaries between the physical and virtual worlds. In this context, cybercrime has emerged as a serious challenge that requires adequate legal handling. This article examines the urgent need for criminal law reform in Indonesia to anticipate and respond to cybercrime in the Society 5.0 era. Through normative analysis and review of existing policies, this study assesses the effectiveness of current regulations. The proposed reforms include strengthening a legal framework that is more adaptive to technological innovations, increasing the capacity of law enforcement in dealing with digital crimes, and adjusting penalties for crimes that occur in cyberspace. The article also highlights the importance of international collaboration in cyber law enforcement. In conclusion, without a comprehensive reform of the criminal law, Indonesia risks falling behind in efforts to deal with the threat of cybercrime in the Society 5.0 era.